PENGEMBANGAN E-MODUL BERBANTUAN FLIPBOOK PADA MATERI APLIKASI TURUNAN FUNGSI ALJABAR KELAS XI SMAN 8 LUBUKLINGGAU - M. Rizki Darmansyah; Rani Refianti; As Elly (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The aim of this research is to determine the validity, practicality and effectiveness of the Flipbook-Assisted E-Module on the Algebra Function Derivative Application Material for Class XI IPA 2 SMA Negeri 8 Lubuklinggau. The research used is RD using the ADDIE model. Data collection techniques are interviews, observation, questionnaires and tests. The research subjects were students of class XI Science 2 at SMA Negeri 8 Lubuklinggau.It is-assisted moduleflipbook what was developed was declared valid, this was based on a language validator of 0.86, a media validator of 0.94 and a material validator of 0.95. The results of the validity test recapitulation show a high score with an average of 0.91. The teacher's practicality result is 4.85, testone to one evaluation was 4.52, small group practicality was 4.31, it was concluded thatIt is-assisted moduleflipbook in the application material for algebraic function derivatives, it shows an average score of 4.56 and is said to be practical. Effectiveness based on scoreN-gain amounting to 0.71 in the high category. therefore it is concluded thatIt is-The flipbook-assisted module on the application of algebraic function derivatives developed is valid, practical and effective.